Nourished Planet Sustainability in the Global Food System - Barilla Center for Food and Nutrition (Island Press/Center for Resource Economics, 2018)
Mangos from India, pasta from Italy, coffee from Colombia: Every day, we are nourished by a global food system that relies on our planet remaining verdant and productive. But current practices are undermining both human and environmental health, resulting in the paradoxes of obesity paired with malnutrition, crops used for animal feed and biofuels while people go hungry, and more than thirty percent of food being wasted when it could feed the 795 million malnourished worldwide. In Nourished Planet, the Barilla Center for Food & Nutrition offers a global plan for feeding ourselves sustainably. Drawing on the diverse experiences of renowned international experts, the book offers a truly planetary perspective. Essays and interviews showcase Hans Herren, Vandana Shiva, Alexander Mueller, and Pavan Suhkdev, among many others. Together, these experts plot a map towards food for all, food for sustainable growth, food for health, and food for culture. With these ingredients, we can nourish our planet and ourselves.